Pemanfaatan Limbah untuk Penyiraman Ruang Terbuka Hijau dalam Perencanaan Pembangunan Rumah Sakit di Jawa Timur - Putri Safa, Alodisa; Lukita, Cesaria Wahyu; Ardisty Sitogasa, Praditya Sigit (Jurnal Serambi Engineering, 2025)
This study aims to assess the utilization of wastewater managed through the Wastewater Treatment Plant (WWTP) as a source of watering Green Open Space (RTH) in the planning of health facility development in the East Java region. The research method includes literature study, primary and secondary data collection, quantitative analysis, and preparation of this study. The results of this study show that the average clean water demand of 58.02 m³/day produces liquid waste of 53.38 m³/day. After being treated through the WWTP, the liquid waste in the form of gray water as much as 42.70 m³/day is utilized for watering green spaces covering an area of 10,675.68 m². This system supports water use efficiency of up to 100% by utilizing treated water for irrigation needs, especially during the dry season. This study concludes that the utilization of WWTP effluent for soil application can be an effective and sustainable solution in hospital wastewater management.